PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN - Prasetio, Ferandi; Rahardja, Rahardja (Diponegoro Journal of Accounting, 2015)
This study aims to analyze and provide empirical evidence of the influence ofintellectual capital to company’s financial performance. Hypothesis (1) Intellectual Capital affect to company’s financial performance, (2) Intellectual Capital positively affect company’s financial performance for upcoming year.This study uses secondary data to the entire population of banks and insurance companies listed in Indonesia Stock Exchange (IDX) 2011-2013. The method used to determine study sample was purposive sampling method, in order to obtain 114 sample companies, which each year is composed of 38 companies. The method of analysis used in this study is Partial Least Square (PLS).The result shows that intellectual capital have effect to company’s financial performance and company’s financial performance for upcoming year